Psychological wellbeing and mental health screening among cancer patients - Wong, Wing Hoe; Mohd Noah, Sidek; Ismail, Asmah (Human Resource Management Academic Research Society, 2017)
The study examined the cancer patients’ psychological wellbeing and the need for mental health screening among cancer patients undergoing cancer related treatments. This research was conducted on 240 cancer patients (120 male and 120 female) from the Department of Radiotherapy and Oncology, Hospital Kuala Lumpur. This study used the Depression, Anxiety, and Stress Scale (DASS) as an instrument for mental health screening and data collection. Both descriptive and statistical analyses were performed on the data using mean, frequency, percentage, and independent sample t tests. Findings show that female participants recorded higher prevalence rates of symptoms related to depression, anxiety, and stress. Statistical analyses indicate there are significant differences in mean scores of depression, anxiety, and stress between genders. Implications of the research and suggestions for further study are also discussed.